Uses and gratification of the star online facebook page - Pariyadan, Jeevanaraj; Adzharuddin, Nor Azura (Medwell Online, 2017)
News organizations starts using social media as news delivery channels and audience reach. The star is one of the leading newspapers in the country and utilize the social media to communicate with the readers with >200,000 likes. The present study aimed to test the perceptions on four factors of gratification (contribution, discovery, social interaction and entertainment) among the star online Facebook page likers. A total 92 Facebook users was selected randomly from list of personal liked the page. A set of web-based questionnaire was email to the respondent’s Facebook personal messaging system. Results show that television and newspaper are still being utilized despite the emerging of online news media portals in the country. Furthermore, entertainment is the top most priority for an individual to assess to media. There were three uses and gratification factors extracted. Users acknowledged that they valued the star online Facebook page because it helped them to keep up with the unexpected stories around the world and provide entertaining news. While social interaction has always affected the dissemination of news, the study suggests that social media are becoming central to the way people experience news. The study contributes to our understanding of the evolving relationship between the organization’s online media tool and the audience.